Nutritional Health Status of Primary School Children: A study in Bareilly District - Mehrotra, Monika; Arora , Santosh; Nagar, Veenu (INDIAN EDUCATIONAL REVIEW, 2011)
The future of the society depends on the quality of life of the children. Nutritional needs change throughout life, depending on genetics, rate of growth, activity and many other factors. Nutritional status is the condition of health of the individual as influenced by the utilisation of nutrients. Nutritional needs also vary from individual to individual. The major objective of this research is “to assess the nutritional health status of primary school children of rural and urban areas”, by assessing their clinical health status and the quantity and quality of food intake by the children in both the areas of study. Four hundred children of 7-9 years of age were selected from the rural and urban areas of Bareilly district. They were assessed for nutritional health status by applying Clinical Nutrition Survey Chart; 24-hr recall method and Food Frequency Questionnaire. The nutritional deficiency signs and symptoms were observed more in rural children than the urban children. Nutrient intake and consumption frequency of all the 6 food groups was more among the urban children compared to their rural counterparts.